1998
DOI: 10.1128/aac.42.10.2650
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of Gatifloxacin in Cerebrospinal Fluid in Experimental Cephalosporin-Resistant Pneumococcal Meningitis

Abstract: The purpose of this study was to evaluate the cerebrospinal fluid (CSF) pharmacodynamics of a new fluoroquinolone, gatifloxacin (AM-1155), in experimental pneumococcal meningitis. The penetration of gatifloxacin into CSF, calculated as the percentage of the area under the concentration-time curve (AUC) in CSF over the AUC in blood, was 46 to 56%. Gatifloxacin showed linear pharmacokinetics in CSF, and 1 h after intravenous dosages of 7.5, 15, or 30 mg/kg of body weight, peak CSF concentrations were 0.46 ± 0.08… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…For example, in a study of rats treated with lomefloxacin for pseudomonal sepsis, no differences were reported among C max /MIC, AUC/MIC and T eff , as predictors of survivorship; the coefficients of determination (r 2 ) were 0.99, 0.99, and 0.98, respectively [35]. Similar predictive potentials of the MBC analogues of these predictors were reported in rabbits with pneumococcal meningitis that were treated with gatifloxacin (r 2 s of 0.74, 0.69, and 0.68, respectively) [39]. Also, no significant differences were observed between the predictive forces of log C max /MIC and T eff of gemifloxacin [40] in murine models of thigh or lung infections caused by Streptococcus pneumoniae (r 2 of 0.53 and 0.48, respectively) and Klebsiella pneumoniae (r 2 of 0.72 and 0.59 to 0.85, respectively).…”
Section: Predictors Of the Antimicrobial Effectsupporting
confidence: 67%
“…For example, in a study of rats treated with lomefloxacin for pseudomonal sepsis, no differences were reported among C max /MIC, AUC/MIC and T eff , as predictors of survivorship; the coefficients of determination (r 2 ) were 0.99, 0.99, and 0.98, respectively [35]. Similar predictive potentials of the MBC analogues of these predictors were reported in rabbits with pneumococcal meningitis that were treated with gatifloxacin (r 2 s of 0.74, 0.69, and 0.68, respectively) [39]. Also, no significant differences were observed between the predictive forces of log C max /MIC and T eff of gemifloxacin [40] in murine models of thigh or lung infections caused by Streptococcus pneumoniae (r 2 of 0.53 and 0.48, respectively) and Klebsiella pneumoniae (r 2 of 0.72 and 0.59 to 0.85, respectively).…”
Section: Predictors Of the Antimicrobial Effectsupporting
confidence: 67%
“…If a drug is to be used effectively, it is important to investigate its pharmacokinetics in each animal species and the climate in which the drug is to be used clinically (Nawaz et al, 1980). Accordingly, pharmacokinetic studies of gatifloxacin have been conducted in humans (Nakashima et al, 1995), rabbits (Lutsar et al, 1998) and mice (Andes and Craig, 2002). However, there is no information available on the pharmacokinetics of gatifloxacin in buffalo species.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies in pneumococcal meningitis have also shown that a maximal bactericidal efficacy is obtained when the concentration of the fluoroquinolones in CSF exceed the MBC (or MIC) during the entire dosing interval [50]. This feature is probably due to the short sub-MIC effect (postantibiotic effect) of quinolones against pneumococci [49,50]. In an in vitro pharmacodynamic model, the importance of T > MBC has also been demonstrated for quinolone therapy against gram-negative pathogens [51].…”
Section: Pharmacodynamic Parametersmentioning
confidence: 93%